Rare Presentation of Metastatic Lobular Breast Carcinoma Involving Clear Cell Renal Cell Carcinoma - Dayne Ashman; Gabriela Quiroga-Garza; Daniel Lee (Case Reports in Oncological Medicine)
Although the first case of tumor-to-tumor metastasis was reported over a century ago, it remains a rare occurrence. We report a rare case of metastatic infiltrating lobular carcinoma involving clear cell renal cell carcinoma, as well as offer a brief literature review.